Chitosan–Zein Films Decorated with Green Synthesized Silver Nanoparticles Using Bergenia ciliata Extract - Ananda Bahadur Chand; Moses Ashie; Rabin Dahal; Ram Datt Joshi; Arjun Prasad Tiwari; Mahesh Kumar Joshi; Bishnu Prasad Bastakoti; Surya Kant Kalauni (Molecules)
This study reports on the fabrication of chitosan-zein films decorated with silver nanoparticles synthesized via a green and eco-friendly approach using an extract of Bergenia ciliata. The strong reducing ability and caping properties of the phytochemicals present in the extract enabled the formation of silver nanoparticles with an average diameter of ~40 nm without any external reducing agent and stabilizer. The uniformly distributed Ag nanoparticles were embedded in the chitosan-zein matrix. The structural and morphological characteristics of the film were analyzed via Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, X-ray diffractometry, scanning electron microscopy, and transmission electron microscopy. The silver nanoparticles decorated with chitosan-zein films showed thermal stability, durability, and excellent antimicrobial activities. This finding demonstrates a sustainable and green pathway for developing multifunctional nanocomposite films, contributing to the advancement of bio-based materials for prospective therapeutic applications and active food packaging.